BEHAVIOR ANALYSIS OF COCOA MARKET IN THE DISTRICT PIDIE JAYA - Jafaruddin Jafaruddin; Rosmaniar Rosmaniar; Adhiana Adhiana; Suryadi Suryadi; Jamilah Jamilah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to examine the behavior of the cocoa market in Pidie Jaya Regency, using a qualitative descriptive approach and a quantitative descriptive approach. Determination of the sample of farmers using simple random sampling method, while the determination of the sample of traders using the technique of snowball sampling. The results showed that there was a tendency for farmers to sell cocoa to village collectors compared to sub-district traders because of limited transportation facilities at the location of the land. There is collusion and strategies by farmers and traders in cocoa marketing. There is a tendency for traders to determine cocoa price standards among traders and set a minimum price for farmers, so that farmers are disadvantaged. This condition shows the existence of information asymmetry related to low selling prices for farmers and is detrimental to farmers